Presidential misconduct : from George Washington to today - Banner, James M., Jr., 1935- (New Press, 2019)
"A reissue of the 1974 report for the House Committee on the Judiciary updated to cover presidents Nixon through Obama"-- Provided by publisher
"The introduction by C. Vann Woodward and the chapters from George Washington through Lyndon B. Johnson were originally published in the United States as Responses of the Presidents to Charges of Misconduct by Dell Publishing Co., Inc., New York, 1974"--Title page verso
Keywords: Political corruption -- United States -- History.; Misconduct in office -- United States -- History.; Presidents -- United States -- History.; Corruption (Politique) -- États-Unis -- Histoire.; Prévarication -- États-Unis -- Histoire.; Présidents -- États-Unis -- Histoire.; HISTORY -- United States -- State & Local -- General.; Misconduct in office; Political corruption; Presidents; United States; HISTORY / United States / General; History